Advances in sago palm research: a comprehensive review of recent findings - Fifi Hafizzah Pendi,; Yan, Wei-Jie; Hasnain Hussain,; Hairul Azman Roslan,; Norzainizul Julaihi, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The sago palm (Metroxylon sagu Rottb.) is an indigenous plant in Papua New Guinea, Indonesia, Malaysia, and Thailand. It provides substantial needs to the locals, especially through the starch it produces in its trunk. Exhibiting remarkable adaptability, this palm can thrive in challenging environments like swamps and peat soils. This paper provides an overview of the molecular methods previously utilised to decipher the genes responsible conferring the characteristics of sago palm molecular techniques employed to investigate M. sagu molecular properties include molecular markers, genome walking, rapid amplification of cDNA ends (RACE), polymerase chain reaction (PCR) and sequencing. Additionally, this article presents other molecular techniques that can be applied to M. sagu for future crop breeding.